The best of me - Sparks, Nicholas (Grand Central Publishing, 2011)
This is the story of two small-town former high school sweethearts from opposite sides of the tracks. Now middle-aged, they have taken wildly divergent paths, but neither has lived the life they imagined, and neither can forget the passionate first love that forever altered their world. When they are both called back to their hometown for the funeral of the mentor who once gave them shelter, they will be forced to confront the choices each has made, and ask whether love can truly rewrite the past.